Bibliotheca Nationis Hungariae: A Wittenberg-Hallei Magyar Könyvtár mint a kora újkori evangélikus peregrináció lenyomata - Csepregi, Zoltán (Studia Litteraria, 2026)
The library in Halle today is the most important organically structured collection of early modern Hungarian peregrination outside the Carpathian Basin. The manuscript collection of the Hungarian Library of Wittenberg-Halle identifies some 3000 early modern individuals (authors, recipients, copiers, possessors). e types of documents (letters, albums, lecture notes), together with occasional printed material, are excellent for analysing the network of contacts and evaluating the content of studies abroad. The collection also includes the administration of scholarships for students in Hungary (applications, decisions, accounts), and the documentation of book acquisitions (last wills, book donations, catalogues). The study aims to outline new research possibilities, while taking stock of the results to date.